Reuse of Decommissioned Wind Turbine Blades in Pedestrian Bridges - Detailed investigation of deflection and dynamic response - Härnborg, Christoffer; Dahlén, Johan (My University, 2021)
The increasing demand for sustainable energy has led to a rapid growth of wind turbine production. Since wind turbine blades are mainly composed of glass fibre reinforce polymers, which has no viable recycling methods, measures to reuse the blades is necessary to deem the energy production method as a sustainable long term solution. One possibility is to utilise the wind turbine blades as structural components for pedestrian bridges. Serviceability deflections and vibrations is stud ied to verify the viability of the concept. There are ongoing projects investigating how wind turbine blades can be used for bridge applications, however, little to no dynamic calculations have been performed. Within the wind turbine blade manufacturing industry there is a corporate secrecy regarding blade design and material constituents due to competitive purposes. This aggravates the existing difficulties of performing accurate analyses of the decom missioned blades for pedestrian bridge applications. However, a data sheet of a 28.3-meter-long wind turbine blade was supplied by its manufacturer which allows for detailed verification validating the models in the present work. To investigate the response for several sections with different lengths extracted from different po sitions of the blade a parametric script was written. The script is compatible with the finite element software BRIGADE/Plus used for the analyses. The analyses performed conclude that there might be possibilities of utilising the blades for structural members for pedestrian bridges. For the specific blade and bridge configuration studied, blade sections up to 14.0 meters show promising re sults and may be possible to proceed with construction. However, it is necessary to note that the longer sections require the stiffest and also largest parts of the blade to be used. Furthermore, when performing sensitivity analyses it was noticed that the results are largely dependent on assumed damping ratio and stiffness properties which are difficult to confidently assess. To validate each concept full-scale testing may be necessary both to validate the material properties and subsequently the dy namic behaviour of the constructed bridge.
Keywords: Wind turbine blades, Fibre reinforced polymer (FRP), Pedestrian bridge; Dynamic response, Finite element analysis, Parametric scripting